2001
DOI: 10.1007/s00418-001-0333-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular polymorphism of the intermediate filament protein transitin

Abstract: Transitin is an avian intermediate filament protein whose transient expression in the progenitor cells of the muscle and nerve tissues is similar to that of mammalian nestin. Both proteins contain an alpha-helical core domain flanked by a short N-terminal head and a long C-terminal extremity. However, the tail region of transitin is significantly different from that of nestin in that it harbors a unique motif containing more than 50 leucine zipper-like heptad repeats which is not found in any other intermediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…During the past decade, several studies have contributed to the analysis of neural developmental processes in the chicken embryo, such as neurogenesis, migration, and patterning (Itasaki etal., 1999; Stern, 2005; Lu et al, 2009). Some neural IF genes of the chicken have been cloned and characterized (Zopf et al, 1987; Shaw, 1989; Henion et al, 2000; Darenfed et al, 2001; Wakamatsu et al, 2007). However, little is known about the sequence, structure, expression patterns, and function of the neuronal IF α‐internexin gene in avians.…”
mentioning
confidence: 99%
“…During the past decade, several studies have contributed to the analysis of neural developmental processes in the chicken embryo, such as neurogenesis, migration, and patterning (Itasaki etal., 1999; Stern, 2005; Lu et al, 2009). Some neural IF genes of the chicken have been cloned and characterized (Zopf et al, 1987; Shaw, 1989; Henion et al, 2000; Darenfed et al, 2001; Wakamatsu et al, 2007). However, little is known about the sequence, structure, expression patterns, and function of the neuronal IF α‐internexin gene in avians.…”
mentioning
confidence: 99%
“…Its expression in radial glia at apparent sites of cell-substratum adhesion and the localization of its mRNA to radial glia endfeet (Lee and Cole, 2000) are suggestive of local regulation of transitin concentration in specific distal compartments. In addition, our laboratory demonstrated that a subset of transitin molecules is concentrated in a submembranous domain of migrating neural crest cells in vitro (Darenfed et al, 2001). Immunoreactivity of this submembranous domain rapidly disappeared from points of cell-cell contacts when avian QM7 myoblasts were induced to fuse and differentiate into myotubes.…”
Section: Introductionmentioning
confidence: 92%
“…Localization of transitin mRNA in radial glia processes of the developing chick CNS and to Z-lines in developing skeletal muscles (Lee and Cole, 2000) suggests that transitin concentration may be regulated in specific distal compartments. In QM7 cells, we have previously shown that a subset of transitin molecules, defined by mAb A2B11, concentrated in a submembranous domain distinct from the pool of transitin molecules associated to the IF network (Darenfed et al, 2001). When QM7 cells were induced to differentiate by switching to DM, an early effect was the local loss of A2B11 staining at the points of cell-cell contacts.…”
Section: Transitin and Myogenesis 3043mentioning
confidence: 99%
See 1 more Smart Citation
“…Transitin represents an avian intermediate filament with transient expression in progenitor cells of muscle and nerve tissues. Its expression during in vitro myogenesis of the quail myogenic cell line QM7 was studied by confocal immunofluorescence (Darenfed et al 2001).…”
Section: Histochemistry As Applied To Studies Of Cell and Organ Diffementioning
confidence: 99%